Holocaust representation : art within the limits of history and ethics - Lang, Berel (John Hopkins paperback., 2000)
"Berel Lang addresses the relations between ethics and art in the context of contemporary discussions of the Holocaust. Are certain aesthetic means or genres "out of bounds" for the Holocaust? To what extent should artists be constrained by the "actuality" of history - and is the Holocaust unique in raising these problems of representation?"--Jacket